MITOS DALAM LEGENDA KERAJAAN PULAU HALIMUN DI KABUPATEN KOTABARU - Normasunah Normasunah (STKIP Paris Barantai, 2014)
ABSTRACTAs a speech literature, a Myth has a high power of life to unite a community characterized in a same way of life. The Community is a society believing in an irrational matter around them, but it really happens, such as Kotabaru citizen which believes in the legend of Halimun Island Kingdom. The Matters in this research are (1) How is the form of myth in the legend of Halimun Island Kingdom? (2) What is the functions of myth in the legend of Halimun Island Kingdom? And its Purposes are (1) to know the form of myth in the legend of Halimun Island Kingdom, and (2) to know the functions of myth in the legend of Halimun Island Kingdom.This research is a qualitative research using analysis and field descriptive method. The way of Data analysis in this research is using Levi-Strauss Linguistic Model. In the analysis of the myth, Levi-Strauss suggests two steps of analysis and interpretation, they are to compare the myths with another myths, to seek a ethnographic connection among people who believe in it. The data of this research is a literature of Myths in the Legend of Halimun Island Kingdom. First version of myth literatures in this research is taken from Myth literatures of Sambu Ranjana that nowday is known as Saranjana Mountain. Second version of myth literatures used for this research is taken from Myth literatures of Sambu Batung that nowday is known as Sebatung Mountain. The sources of both is exactly taken from speech literature which grown around people in Kotabaru.Legend of the Kingdom of Island Mist is one of folklore in Kotabaru district. The results of this study berfokos on the form and function of myth in the Legend of the Kingdom of Island Mist in Kotabaru district. The form of myth in this study looks at the incarnation Sambu Ranjana is now better known as mountain Saranjana and Sambu Batung which was transformed into a mountain Sebatung. The function of myth in this study are (1) the political function of the myth (2) Function mite (believing in the myth of the nature of thought based on the mystical perception, without believing that the real object) The function is a myth in the study of information that should be known by the public Kotabaru , During this time many people believe their only Kotabaru magical city that makes Kotabaru known by the humanists without knowing his legend. Mount saranjana is one of the magical city that is well known by its myth. Therefore, the lack of research on the myth in this LKPH can demonstrate to the public to be more aware Kotabaru own region.Â Keyword: Myth, Legend, Halimun Island.